Molecular Structure, Expression and Role of TAFA4 and its Receptor FPR1 in the Spinal Cord - Zhu, Sipin; Hu, Xiaoyong; Bennett, Samuel; Mai, Yuliang; Xu, Jiake (Frontiers in Cell and Developmental Biology, 2022)
TAFA chemokine like family member 4 (TAFA4, also named FAM19A4) is a member of the TAFA chemokine like ligand or FAM19A family, which includes TAFA1, TAFA2, TAFA3, TAFA4, and TAFA5 (or FAM19A1, FAM19A2, FAM19A3, FAM19A4, and FAM19A5). They are also referred to as neurokines and are involved in the regulation of a diverse range of cellular processes, including chemotaxis of macrophages, phagocytosis, and release of reactive oxygen species (ROS). TAFA4 is a marker of C-low-threshold mechanoreceptors and is expressed predominantly in nociceptors, such as dorsal root ganglia (DRG). TAFA4 has been implicated in the sensory perception of pain in the spinal cord. Mice with deficiency of TAFA4 demonstrate altered excitability in lamina IIi neurons in DRG in addition to increased mechanical and chemical nociception following inflammation or injury. As a secreted protein, TAFA4 binds to cell surface receptor formyl peptide receptor 1 (FPR1), a G protein-coupled receptor to mediate the chemoattraction of macrophages, phagocytosis, and the inflammatory profile of macrophages. It also interacts with cell surface neurexin to mediate signalling across the synapse. Further understanding the mechanisms by which this conserved protein family regulates diverse biological processes such as in neuronal functions, inflammation, and tissue fibrosis will help to design therapeutic targets for the treatment of TAFA related diseases such as spinal cord injury and neuro-inflammatory disorders.